2015
DOI: 10.2147/ijn.s70503
|View full text |Cite
|
Sign up to set email alerts
|

Accessing to the minor proteome of red blood cells through the influence of the nanoparticle surface properties on the corona composition

Abstract: Nanoparticle (NP)–protein interactions in complex samples have not yet been clearly understood. Nevertheless, several studies demonstrated that NP’s physicochemical features significantly impact on the protein corona composition. Taking advantage of the NP potential to harvest different subsets of proteins, we assessed for the first time the capacity of three kinds of superparamagnetic NPs to highlight the erythrocyte minor proteome. Using both qualitative and quantitative proteomics approaches, nano-liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…( Supplementary Figure S1 (Supplementary Materials) ). We have also assessed the potential blood contamination in the CSF samples by examining the molecules enriched in red blood cells [ 60 , 61 , 62 , 63 ], and only hemoglobin beta (HBB) and peroxiredoxin-2 (PRDX2) were identified in the proteomic profiles of CSF EVs ( Supplementary Figure S2 (Supplementary Materials) ). There was no statistical significance in the amount of HBB or PRDX2 among the 3 groups and no outlier was detected, ruling out the possibility of blood contamination.…”
Section: Resultsmentioning
confidence: 99%
“…( Supplementary Figure S1 (Supplementary Materials) ). We have also assessed the potential blood contamination in the CSF samples by examining the molecules enriched in red blood cells [ 60 , 61 , 62 , 63 ], and only hemoglobin beta (HBB) and peroxiredoxin-2 (PRDX2) were identified in the proteomic profiles of CSF EVs ( Supplementary Figure S2 (Supplementary Materials) ). There was no statistical significance in the amount of HBB or PRDX2 among the 3 groups and no outlier was detected, ruling out the possibility of blood contamination.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al (8) and Cederfur et al (9), using LC-MS/MS, also found that the majority of the differentially expressed proteins in asthmatic RTLFs were associated with immune response (23%), lipid metabolism (12%) and proteolysis (9%). Thus, the coronal proteome appears to represent a concentrated fingerprint reflecting underlying protein composition of the host RTLF (10). Differences between the corona formed in healthy and asthmatic RTLF were evaluated further using iPathwayGuide analysis to obtain biological insights by identifying the pathways/functions most impacted by the observed changes between the two groups.…”
Section: Short Communicationmentioning
confidence: 99%
“…Indeed, even though pioneering studies from Anniss and colleagues have paved the way for in‐depth investigations of the storage lesion to the proteomes of RBC membranes and supernatants, RBC proteomics studies performed so far have primarily relied on qualitative or relative quantitation technologies. Fostered by critical advances in the field of mass spectrometry (MS)‐based RBC proteomics, light has been shed on the unanticipated complexity of the RBC proteome in the past decade and a half. Such data have paved the way for the bioinformatics elaboration of RBC protein and metabolic interaction pathways, a key reference database for hypothesis‐driven research in the field.…”
mentioning
confidence: 99%